2016
DOI: 10.1002/mabi.201600159
|View full text |Cite
|
Sign up to set email alerts
|

RGDS- and SIKVAVS-Modified Superporous Poly(2-hydroxyethyl methacrylate) Scaffolds for Tissue Engineering Applications

Abstract: Three-dimensional hydrogel supports for mesenchymal and neural stem cells (NSCs) are promising materials for tissue engineering applications such as spinal cord repair. This study involves the preparation and characterization of superporous scaffolds based on a copolymer of 2-hydroxyethyl and 2-aminoethyl methacrylate (HEMA and AEMA) crosslinked with ethylene dimethacrylate. Ammonium oxalate is chosen as a suitable porogen because it consists of needle-like crystals, allowing their parallel arrangement in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
0
15
1
Order By: Relevance
“…In another study, to improve the interaction of the super‐porous copolymer hydrogel scaffolds HEMA and AEMA with hMSCs and human fetal NSCs, the Ac‐CGGASIKVAVS‐OH (SIKVAV) peptide was covalently attached to the copolymer. It has been shown that the adhesion of hMSCs markedly improved on SIKVAVSP (HEMA‐co‐AEMA) compared with that on pure P (HEMA‐co‐AEMA) scaffolds . A hydrogel scaffold of well‐defined geometry was created by modifying the P (HEMA‐co‐AEMA) scaffold with covalently attached CDPGYIGSR and CQAASIKVAV.…”
Section: Cell Culture and Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, to improve the interaction of the super‐porous copolymer hydrogel scaffolds HEMA and AEMA with hMSCs and human fetal NSCs, the Ac‐CGGASIKVAVS‐OH (SIKVAV) peptide was covalently attached to the copolymer. It has been shown that the adhesion of hMSCs markedly improved on SIKVAVSP (HEMA‐co‐AEMA) compared with that on pure P (HEMA‐co‐AEMA) scaffolds . A hydrogel scaffold of well‐defined geometry was created by modifying the P (HEMA‐co‐AEMA) scaffold with covalently attached CDPGYIGSR and CQAASIKVAV.…”
Section: Cell Culture and Differentiationmentioning
confidence: 99%
“…It has been shown that the adhesion of hMSCs markedly improved on SIKVAVSP (HEMA-co-AEMA) compared with that on pure P (HEMA-co-AEMA) scaffolds. 44 A hydrogel scaffold of welldefined geometry was created by modifying the P (HEMA-co-AEMA) scaffold with covalently attached CDPGYIGSR and CQAASIKVAV.…”
Section: D Environmentmentioning
confidence: 99%
“…The porogen leaching technique is a well-established effective method of introducing pores of the desired shape, size, and orientation to the gel matrix. With the advantage of ease of use and biological safeness, different materials such as sodium chloride [12], ammonium oxalate crystals [19], and paraffin [20] have been used. However, there are challenges related to appropriate design or porogen packing to achieve connected porosity on one side and a coherent gel matrix on the other side through tuned concentration and the placement of particles in the polymerization mixture [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance cell adhesion and migration into implants, the HA-PH was functionalized with RGD oligopeptide sequence, which has affinity for multiple integrin receptors, and has been previously shown to support effective cell spreading and cytoskeletal organization, as well as cell proliferation. 42 However, an important factor in the establishment of cell adhesion is ligand density, which is, in the case of used HA-PH-RGD derivative, limited to the DS of PH-RGD oligopeptide. Hydrogel containing 20 mg/mL of the new designed HA-PH-RGD conjugate with a DS of 2.5% achieved a concentration of RGD sequence 1 mmol/mL of hydrogel.…”
Section: Discussionmentioning
confidence: 99%